EXPERIMENTAL STUDIES ON PNEUMOCOCCUS INFECTIONS - Strouse, S. (The Rockefeller University Press, 1909)
1. Phagocytosis of pneumococci in vitro runs parallel with phagocytosis in vivo. 2. Virulence depends not only on resistance to phagocytosis, but also on the ability to grow in the body of the animal. 3. The biological reaction of the pigeon to pneumococcus infection does not differ from that of the mouse. 4. The "immunity" of the pigeon to pneumococcus infection is due to its normal high temperature.